HUBUNGAN KONDISI FISIK RUMAH, SARANA AIR BERSIH DAN KARAKTERISTIK MASYARAKAT DENGAN KEJADIAN KUSTA DI KABUPATEN TAPIN KALIMANTAN SELATAN - Norlatifah, .; Sutomo, Adi Heru; Solikhah, . (Universitas Ahmad Dahlan, 2010)
Background: leprosy is a chronic disease caused by the bacteria Mycobacterium leprae theattacks the peripheral nerves, the skin and other tissue except the central nervous system.Indonesia has third position as great number of cases of leprosy after India and Brazil at years2005 there is 19.695 cases. In years 2007, prevalence of leprosy in Indonesia was 1,05 caseper 10.000 population. The Tapin regency was the leprosy endemic area, when years by yearsnewly detected cases. The aim of this research to determine the relationship of physicalcondition of the house, fresh water instalation and characteristic of community with cases ofleprosy in Tapin Regency South Borneo.Method : Analityc observational studies using case-control. The act of determining the casesample is taken by using the totality sample and the act of determining the control sample istaken by using the purposive sample. The case number of 31 people and the control number of62 people.Results: Based on result of bivariate test there are 3 meaningful variables statisticallyrelationship with cases of leprosy in Tapin Regency South Borneo, i.e phisical home condition(p=0,013), history of contact (p=0,000) and level of education (p=0,002). The variables notrelated with cases of leprosy in Tapin Regency South Borneo, i.e fresh water instalation(p=0,099), age (p=0,226) and occupation (p=0,559). The result of multivariate test there are 3the most dominant variable within spread of leprosy in Tapin Regency South Borneo, i.e thehistory of contact (p=0,002), level of education (p=0,006) and phisical home condition (p=0,043).Conclusion: There was significant relation between the phisical home condition, history ofcontact and level of education with cases of leprosy in Tapin Regency South Borneo. Thehistory of contact, level of education and phisical home condition was the most dominant casesof leprosy in Tapin Regency South Borneo.Keyword: home, water, age, contact, education and occupation.